Common reed accumulates starch in its stem by metabolic adaptation under Cd stress conditions - Higuchi, Kyoko; Kanai, Masatake; Tsuchiya, Masahisa; Ishii, Haruka; Shibuya, Naofumi; Fujita, Naoko; Nakamura, Yasunori; Suzui, Nobuo; Fujimaki, Shu; Miwa, Eitaro (Frontiers in Plant Science, 2015)
In a previous study, we reported that the common reed accumulates water-soluble Cd complexed with an α-glucan-like molecule, and that the synthesis of this molecule is induced in the stem of the common reed under Cd stress. We studied the metabolic background to ensure α-glucan accumulation under the Cd stress conditions that generally inhibit photosynthesis. We found that the common reed maintained an adequate CO2 assimilation rate, tended to allocate more assimilated 11C to the stem, and accumulated starch granules in its stem under Cd stress conditions. AGPase activity, which is the rate-limiting enzyme for starch synthesis, increased in the stem of common reed grown in the presence of Cd. Starch accumulation in the stem of common reed was not obvious under other excess metal conditions. Common reed may preferentially allocate assimilated carbon as the carbon source for the formation of Cd and α-glucan complexes in its stem followed by prevention of Cd transfer to leaves acting as the photosynthetic organ. These responses may allow the common reed to grow even under severe Cd stress conditions.